Chronic rhinosinusitis in eosinophilic granulomatosis with polyangiitis: clinical presentation and antineutrophil cytoplasmic antibodies. Issue 2 (2nd December 2019) - Low, Christopher M.; Keogh, Karina A.; Saba, Elias S.; Gruszczynski, Nelson R.; Berti, Alvise; Specks, Ulrich; Baqir, Misbah; Smith, Byron M; Choby, Garret; Stokken, Janalee K.; O'Brien, Erin K.
Abstract : Background: In this study we aim to describe presenting characteristics and identify prognostic factors for disease resolution in patients with chronic rhinosinusitis (CRS) in the setting of eosinophilic granulomatosis with polyangiitis (EGPA). Methods: Patients evaluated at a tertiary care center with diagnoses of EGPA and CRS were identified. Descriptive statistics were obtained. Univariate analysis was used to search for prognostic factors associated with higher Lund‐Mackay score at presentation and disease resolution. Results: Forty‐four patients were included with a mean age of 52.7 (standard deviation, 14) years. Twenty‐one patients (47.7%) were female, all had a diagnosis of asthma, and 36 (83.7%) had eosinophils >10%. Common presenting symptoms for CRS included nasal discharge (87.9%) followed by nasal congestion (83.9%) and facial pain and pressure (83.8%). Medical management of CRS included systemic corticosteroids (93.2%) and systemic antibiotics (75%). Surgical intervention occurred in 29 patients (67%). Nine patients (20.5%) had resolution of sinus symptoms, including 4 with imaging confirmation. Fourteen patients (31.8%) had continued CRS, but with improved symptoms, whereas 9 patients (20.5%) had continued CRS with no improvement in symptoms. Eleven patients (25%) were lost to follow‐up and 4 (9.1%) died. Univariate analysis did not show antineutrophil cytoplasmic antibody positivity, presence of peripheral eosinophilia, gender, age, or absence of systemic therapy to be predictive of higher Lund‐Mackay score at presentation or predictive of disease resolution. Conclusion: CRS in patients with EGPA is often refractory to medical and surgical management. Treatment of these patients should occur in a multidisciplinary setting.